English speaking training based on local wisdom to support the English language skills - S. Surayanah; M. Anas Thohir; Lilik Bintartik; Marsanda Avilia Putri; L. Lestariningsih (Research and Development in Education (RaDEn), 2025)
English language skills are essential skills that must be mastered by people in today's digital era, including students. However, students' ability to speak English is still low as evidenced by the results of the UKBing test for Campus 3 students at Universitas Negeri Malang, East Java-Indonesia which is still quite low. The purpose of this research is to develop English Speaking Training (EST) based on local wisdom, looking for its effect on students' English language skills, as well as its correlation with the results of students' English language skills. The research method used is Research & Development (R&D) with the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation. The data obtained in the form of pre-test and post-test results and documentation will be analyzed using the N-Gain test, correlation test, and qualitative descriptive to represent the results of the study. The results showed a significant effect of EST training on students' English language skills. The results of the correlation test show a positive correlation with an idealized level at a significance level of 0.1, and the N-Gain test indicates that the results fall into the tall group with a rate of 88%. That way, this EST training can be a solution in improving students' English language skills so that they can produce graduates who are able to compete globally.